Analytical Methods to Characterize and Purify Polymeric Nanoparticles - Cristina Fornaguera; Conxita Solans (International Journal of Polymer Science)
Advances in polymeric nanoparticles as novel nanomedicines have opened a new class of diagnostic and therapeutic tools for many diseases. However, although the benchtop research studies in the nanoworld are numerous, their translation to currently marketed products is still limited. This lack of transference can be attributed, among other factors, to problems with nanomedicine characterization. Characterization techniques at the nanoscale could be divided in three categories: characterization of physicochemical properties (e.g., size and surface charge), characterization of nanomaterials interactions with biological components (e.g., proteins from the blood), and analytical characterization and purification methods. Currently available literature of this last group only describes methodologies applied for a specific type of nanomaterial or even methods used for bulk materials, which are not completely applicable to nanomaterials. For this reason, the current review aims to become a scholastic guide for those scientists starting in the nanoworld, giving them a description of analytical characterization techniques aimed to analyze polymers forming nanoparticles and possible forms to purify them before being used in preclinical and clinical applications.